Nursing management of a patient receiving Chinese herbal medicine enema treatment for gastrointestinal dysfunction after laparoscopy (中药灌肠技术治疗腹腔镜术后胃肠功能障碍1例的护理) - LIU Shanshan (刘姗姗); ZHENG Hongmei (郑红梅); SUN Pengcheng (孙鹏程); TANG Ling (唐玲); CHEN Hong (陈宏) (中西医结合护理)
This paper reported the nursing experience of a patient undergoing Chinese herbal medicine enema treatment for gastrointestinal dysfunction after laparoscopy for adrenal mass. The patient was diagnosed with intestinal Qi stagnation according to the Traditional Chinese Medicine syndrome differentiation. The Chinese herbal medicine enema technique and coordinated integrated nursing measures were carried out after nursing evaluation. (本文报告中药灌肠技术干预1例右肾上腺肿物患者腹腔镜术后胃肠功能障碍的护理经验。患者经中医辨证属于腑气不通, 在完善护理评估的基础上, 遵医嘱实施中药灌肠技术进行干预, 并配合中西医结合护理。)